On single-time methods in relativistic gravity dynamics - Opanasyuk, Yu.A. (Condensed Matter Physics, 1998)
A short outline of revived methods of an action-at-a-distance description of interacting particles is given. A new approach to the problem of motion in relativistic gravity is discussed. The approach makes an essential use of the predictive relativistic mechanics method with some phenomenological assumptions as to the character of relativistic "forces". The technique of the construction of the approximate solutions for the Currie-Hill equations is proposed. Some recurrent conditions for these solutions are proved to be necessary and sufficient. The generalized Poincare´-invariant equations of motion are derived in post-Newtonian approximations of the phenomenological formulation of the relativistic action-at-a-distance gravity for the closed system of N structureless particles. Connections of these equations with those of the Lagrangian description are discussed. Подано стислий огляд розвитку Пуанкаре-інваріянтних методів опису механічної системи, що ґрунтуються на сучасній концепції прямої взаємодії. Обговорюється певний підхід до проблеми руху в релятивістичній теорії ґравітації. Підхід суттєво використовує методи предиктивної (з єдиним параметром еволюції) релятивістичної механіки із залученням певних феноменологічних припущень щодо характеру релятивістичних “сил”. Доведено необхідні та достатні умови для побудови в межах обговорюваного підходу наближених (у довільному порядку) розв’язків рівнянь Каррі-Хілла. Для замкнутої системи N ґравітуючих безструктурних точкових часток у пост-ньютонівському наближенні запропоновано узагальнені Пуанкаре-інваріянтні рівняння, які можуть застосовуватися при створенні нового, більш загального, формалізму верифікації релятивістичних теорій тяжіння. Обговорюються взаємозв’язки запропонованих рівнянь та рівнянь, що виникають у лаґранжевому формулюванні релятивістичної динаміки.